Barriers of physical activity of women post breast cancer treatment in rural Poland. Issue 6 (3rd June 2019) - Malicka, Iwona; Hanuszkiewicz, Justyna; Woźniewski, Marek
Abstract: Physical activity (PA) is an important element of healthy lifestyle, plays a major part in primary and secondary prevention of environmental illness. We examined the level of PA over a period of 7 days using Silva ex3 Connect pedometers in women after breast cancer treatment (BCT). Participants were selected from rural areas with restricted access to recreational and rehabilitative services. Women post BCT exhibited a low level of PA, though not deviating significantly from that of healthy women of the same age. There is a need to increase the level of PA among both: women after BCT and healthy women.